The Influence of Organizational and Personal Factors on Entrepreneurial Intentions of Business Professionals - Keshab Khadka, (Journal of Nepalese Management and Research, 2024)
This study examines the impact of organizational and personal factors on the entrepreneurial of business professionals in the Surkhet District. This research employs an explanatory design, utilizing quantitative data and convenience sampling for data collection and analysis. Primary data were gathered using a survey questionnaire administered to 216 business professionals. Descriptive and inferential statistical methods were applied, including frequency and percentage distributions for demographic data and correlation and regression analyses to investigate the relationships between variables. The findings indicate that an innovative climate significantly enhances entrepreneurial intentions, while technical excellence shows a non-significant relationship with EI. Innovation orientation similarly exhibits minimal impact on EI and is also found to be non-significant. Conversely, job satisfaction emerges as a robust positive predictor of EI. These insights provide valuable implications for business professionals, policymakers, educators, and supportive organizations, guiding efforts to foster an entrepreneurial ecosystem conducive to sustainable business development.